Anomalous Cis‐Conformation Regioselectivity of Heterocycle‐Fused Sc3N@D3h‐C78 Derivatives. (24th February 2021) - Chen, Muqing; Guan, Runnan; Li, Bo; Yang, Le; Niu, Chuang; Jin, Peng; Wang, Guan‐Wu; Yang, Shangfeng
Abstract: Endohedral clusterfullerenes exhibit unique chemical properties due to intramolecular electron transfer of the encaged metal cluster to the outer fullerene cages. We report the synthesis of two Sc3 N@ D 3 h ‐C78 monoadducts 2 a and 2 b through the 1, 3‐dipolar reaction of Sc3 N@ D 3 h ‐C78 with carbonyl ylide bearing anomalous cis ‐conformation regioselectivity. The molecular structures of these monoadducts are unambiguously confirmed by single‐crystal X‐ray crystallography, revealing that both 2 a and 2 b have cis ‐conformations with the furan moiety grafted via [6, 6]‐closed addition patterns. Under the same conditions, the control reaction of C60 with carbonyl ylide affords two monoadducts 3 a and 3 b, which exhibit cis ‐ and trans ‐conformations, respectively, with [6, 6]‐closed addition patterns. According to theoretical calculations, the exclusive formation of the cis ‐only Sc3 N@ D 3 h ‐C78 monoadducts is a consequence of conjunct effects of thermodynamic stability of adducts, the reactivity of the addition site, and the cis ‐dipole intermediate from trans 1 . Abstract : Sc3 N@ D 3 h ‐C78 was reacted with carbonyl ylide to form two isomeric monoadducts 2 a and 2 b bearing anomalous cis ‐conformation regioselectivity and a [6, 6]‐closed addition pattern. Whereas isomeric monoadducts 3 a and 3 b with cis ‐ and trans ‐conformations were produced simultaneously for C60 under the same conditions. Adduct stability, reactivity of the addition site, and the nature of intermediates play a role in the different regioselectivity.